Accounts and accountability: The UK Government's misguided plans to regulate corporate reporting and audit - Jamie Whyte (Institute of Economic Affairs (IEA), 2022)
The failures of BHS in 2016 and Carillion in 2018 prompted the government to launch three inquiries into financial reporting and auditing. Their findings and proposals were collected in the government's 2021 consultation document Restoring Trust in Audit and Corporate Governance. In May 2022, the government published its response to the consultation. Among other things, the government proposes to dictate the content of financial reports, require the 'Big Four' audit companies to undergo internal re-organisations, oblige FTSE 350 companies to appoint two audit companies, and create a regulatory agency with greater powers. Each proposal is harmful. Companies have a commercial interest in supplying investors with any information those investors value more than it costs to produce. Government-mandated information production is sure to be inefficient. The government has failed to demonstrate any market failure in the production of financial information by companies. The proposal to force Big Four audit companies to further separate their audit and non-audit operations is based on a misunderstanding of the incentives created by integration and ignores the market disciplines faced by auditors. The proposal to reduce audit market concentration by forcing FTSE 350 firms to appoint at least one non-Big Four auditor fails to appreciate the genuine benefits of scale in auditors. It also constitutes an outrageous intervention in the decision-making of private enterprises and a state-mandated subsidy for second-tier auditing firms. An enlarged financial reporting regulator with stronger powers will increase legal uncertainty for businesses operating in the UK. Contrary to their intended effect, the government's proposed regulations will make the UK a less attractive place in which to invest.
Keywords: 330; Accounting; Corporate publicity; Auditing; Regulation; Great Britain; Rechnungswesen; Unternehmenspublizität; Wirtschaftsprüfung; Regulierung; Großbritannien